2014
DOI: 10.1039/c3tc31416b
|View full text |Cite
|
Sign up to set email alerts
|

Heating and mechanical force-induced luminescence on–off switching of arylamine derivatives with highly distorted structures

Abstract: A triphenylamine-based organic luminophor (TPA-CO) with a highly distorted structure has been designed and effortlessly obtained by an Ullmann reaction. The luminophor exhibits a stimuli-induced emission enhancement effect and intramolecular charge transfer properties. The fluorescence efficiency of its crystals is dramatically increased from 0.4% to 12.3% upon grinding. The emission enhancement is also realized by a heating process. The "bright" state can recover its original state and turn "dark". The lumine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 48 publications
1
54
0
Order By: Relevance
“…Similar phenomena of incomplete conversion have been observed in other ML systems. 17 Annealing or vapour fuming of the ground power results in the disappearance of the diffuse halo and the intensification of diffraction peaks, indicating the recovery of original crystalline state. From the PXRD results, it can be concluded that the conversion between crystalline and amorphous states is responsible for the reversible mechanochromism of TPAANDCV.…”
Section: Luminescence Mechanochromismmentioning
confidence: 99%
“…Similar phenomena of incomplete conversion have been observed in other ML systems. 17 Annealing or vapour fuming of the ground power results in the disappearance of the diffuse halo and the intensification of diffraction peaks, indicating the recovery of original crystalline state. From the PXRD results, it can be concluded that the conversion between crystalline and amorphous states is responsible for the reversible mechanochromism of TPAANDCV.…”
Section: Luminescence Mechanochromismmentioning
confidence: 99%
“…Chemicals and Instruments 1 HNMR and 13 CNMR spectra of the products were recorded on aB ruker AVANCE III 500-MHz instrument (Bruker,S witzerland) with tetramethylsilane (TMS) as the internal standard and chloroform-d (CDCl 3 )ast he solvent, which were purchased from Alfa Aesar.M ass spectrometry (MS) was performed with aT hermo DECAX-60000 LCQ Deca XF (Thermo, USA) mass spectrometer.F luorescence measurements were recorded on aH itachi F-4600 spectrophotometer.T he UV/Vis spectra were recorded with aU V-1800 UV/Vis spectrophotometer (Shimadzu, Japan). Photoluminescence (PL) quantum yields (F f )int he solid state were measured with aHamamatsu absolute PL quantum yield spectrometer C11347 (Quantaurus-QY,J apan).…”
Section: Methodsmentioning
confidence: 99%
“…1 HNMR (500 MHz,CDCl 3 ) d = 8.35 (s, 1H), 8.19 (d,J = 8.0 Hz,1H),7.62 (m,7H),3H),7.46 (dd,J = 9.0,6H),7.39 (d,J = 8.5 Hz,2H),2H),2H), (m, 2H),7.14-7.10 ppm (m, 2H). 13 CNMR (500 Hz, CDCl 3 ): d = 157. 4, 141.9, 141.5, 140.7, 139.4, 137.6, 133.0, 132.2, 130.8, 130.2, 130.0, 129.0, 128.8, 128.5, 128.4, 127.6, 127.1, 126.3, 125.2, 123.5, 120.4, 120.2, 118.7, 111.6, 110.1, 110.0 Crystallographic data for TPAN-C3:C 39 H 27 N 2 ,C 39 H 27 N 2 ,M = 522.62 gmol À1 ,T riclinic, a = 9.818(3), b = 12.379 (12) , c = 13.079 (13) ; b = 69.174(16) , V = 1437(2) 3, T = 293(2) K, R(int) = 0.0367, space group P À1 , D cal = 1.208 gcm…”
Section: Synthesis and Crystal Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the crystalline states of these luminogens may adopt a more twisted conformation and thus excited energy is partially consumed by nonradiative transitions. Upon grinding, the molecular structures become slightly more planar and the effective intramolecular conjugation increases, which further blocks the nonradiative deactivation pathways . Also, the neighboring molecules do not get close to one another due to the steric effect of the substituents, which weakens the intermolecular interactions.…”
Section: Resultsmentioning
confidence: 99%